2013
DOI: 10.1038/jp.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of clonidine versus phenobarbital in reducing neonatal morphine sulfate therapy days for neonatal abstinence syndrome. A prospective randomized clinical trial

Abstract: Phenobarbital as adjunct had clinically nonsignificant shorter inpatient but significant overall longer therapy time as compared with clonidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 29 publications
1
57
1
Order By: Relevance
“…45 However, these studies combined clonidine with morphine, and the concern for potential detrimental effects of continuing postnatal opiate exposure remains. 27 We observed a longer duration of treatment than those reported in combination therapy 25,45 ; this outcome may be related to the single-drug therapy. In addition, the dose for this study is at the lower end reported in the literature, especially for clonidine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…45 However, these studies combined clonidine with morphine, and the concern for potential detrimental effects of continuing postnatal opiate exposure remains. 27 We observed a longer duration of treatment than those reported in combination therapy 25,45 ; this outcome may be related to the single-drug therapy. In addition, the dose for this study is at the lower end reported in the literature, especially for clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,45 Clonidine as adjunctive therapy for NAS was associated with a decrease in the number of morphine doses, duration of treatment, or length of hospital stay. 25,45 From a recent randomized trial, clonidine given with morphine resulted in a shorter duration of therapy compared with the morphine and phenobarbital combination. 45 However, these studies combined clonidine with morphine, and the concern for potential detrimental effects of continuing postnatal opiate exposure remains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies yielded contradictory results in evaluating the efficacy of adjunctive treatment with phenobarbital and clonidine; however, a 2010 Cochrane Review of six studies concluded that addition of phenobarbital or clonidine may reduce duration of treatment for NAS 63. These medications have also been compared directly to one another (in combination with morphine) 64. Surran et al 64 found that infants receiving adjunctive treatment with phenobarbital had a shorter duration of hospitalisation than those adjunctively treated with clonidine, notably, however, infants were discharged home on phenobarbital resulting in a much longer duration of treatment.…”
Section: Neonatal Managementmentioning
confidence: 99%
“…These medications have also been compared directly to one another (in combination with morphine) 64. Surran et al 64 found that infants receiving adjunctive treatment with phenobarbital had a shorter duration of hospitalisation than those adjunctively treated with clonidine, notably, however, infants were discharged home on phenobarbital resulting in a much longer duration of treatment.…”
Section: Neonatal Managementmentioning
confidence: 99%